Glaciers and the Polar Environment - Kanao, Masaki; Godone, Danilo; Dematteis, Niccolò (IntechOpen, 2021)
Glaciers and Polar regions provide important clues to understanding the past and present status of the Earth system, as well as to predict future forms of our planet. In particular, Antarctica, composed of an ice-covered continent in its center and the surrounding Sothern Ocean, has been gradually investigated during the last half century by all kinds of scientific branches; bioscience, physical sciences, geoscience, oceanography, environmental studies, together with technological components. This book covers topics on the recent development of all kinds of scientific research on glaciers and Antarctica, in the context of currently on-going processes in the extreme environment in polar regions.